Sources of economic growth and productivity induced innovation and technological change biases in the agricultural sector - Lanteri, Luis N. (1994)
In this study, we show the differences in output and in output per worker between Argentina and the United States between 1950 and 1990 (1992). In accordance with the labor productivity identity (Y/L = A/L * Y/A), a higher level of labor productivity can be achieved through either an increasing of the land-labor ratio, higher land productivity, or both. In spite of land and labor relative endowment has been similar in Argentina and in the United States, Argentina has achieved higher labor productivity through higher land productivity.